Massive pseudoaneurysm caused by fabric tear of a thoracic endovascular aortic repair stent graft 15 years after the initial procedure - Kotaro Mukasa, MD; Yasunori Yakita, MD, PhD; Musashi Tsuda, MD; Shinichiro Abe, MD, PhD; Soichi Asano, MD, PhD (Journal of Vascular Surgery Cases and Innovative Techniques, 2025)
Long-term durability of thoracic endovascular aortic repair remains uncertain, and late type IIIb endoleak due to fabric tear is a serious concern. We report a 59-year-old man who presented with progressive back pain and a large pseudoaneurysm 15 years after the initial procedure for a ruptured thoracic aneurysm. Intraoperative angiography localized a type IIIb endoleak that originated from a fabric tear in the third stent segment. Urgent endovascular repair with complete graft relining successfully excluded the endoleak, resulting in symptom resolution and pseudoaneurysm regression. This case underscores the risk of very late type IIIb endoleaks and the need for lifelong imaging surveillance and prompt evaluation of new symptoms.